A Markov‐Based Road Maintenance Optimization Model Considering User Costs. (8th March 2013) - Gao, Hui; Zhang, Xueqing
Abstract User costs of different maintenance actions need to be assessed in road maintenance as well as the maintenance costs. The vehicle operating cost (VOC) and the travel delay cost are two major components of the user costs associated with road maintenance actions. This article simplifies the general calculation models of these two user cost components and develops a multiobjective Markov‐based model to minimize both maintenance cost and user cost subject to a number of constraints including the average annual budget limit and the performance requirement. The road deterioration process is modeled as a discrete‐time Markov process, the states of road performance are defined in terms of the road roughness, and the state transition probabilities are estimated considering the effects of deterioration and maintenance actions. An example is provided to illustrate the use of the proposed road maintenance optimization model. The results show that the optimal road maintenance plan obtained from the model is practical to implement and is cost‐effective compared with the periodical road maintenance plan. The results also indicate that the maintenance cost and the user cost are competitive. When maintenance works are carried out more frequently, the life‐cycle maintenance costs will increase while the life‐cycle user costs will decrease. This is because the VOC contributes the most amount of the user cost and its change has a contrary trend to the change of the maintenance cost over time.